ANALISIS KETERAMPILAN DASAR MENGAJAR MAHASISWA CALON GURU KIMIA BERBASIS MODEL CORE TEACHING STANDARDS PADA MATA KULIAH PPL 1 (MICROTEACHING) UNIVERSITAS MUHAMMADIYAH PONTIANAK - Rusninawiyah Rusninawiyah; Tuti Kurniati; Rizmahardian Azhari Kurniawan (Jurnal Ilmiah Ar-Razi, 2018)
Basic teaching skills of Core Teaching Standards model for prospective Chemistry teachers are important in enhancing the competence as they deal with world of education. This study aimed at determining the process of teaching and learning activities as well as basic teaching skills using Core Teaching Standards among prospective chemistry in Microteaching Program 1 (PPL 1) class at Muhammadiyah University of Pontianak. Using descriptive design and quantitative approach, 16 students participated as the subjects. The techniques used in this research were direct observation and direct communication. The data collection technique included observation sheet and interview guide that covered 10 standards. They were student development, learning difference, learning environment, materials, application of materials, assessment, lesson plan, teaching strategy, professionalism in teaching, and leadership and collaboration. The study reveals that the students gained the highest score on standard 9 (professionalism in teaching) by 81,65% and was considered very good. Whereas, they hed the lowest score on standard 6 (assessment) by 58,21% and was considered fair by 58,21%.Keywords: Core Teaching Standards, basic teaching skills, Microteaching 1 (PPL 1)